Risk Factors and Clinical Course of Patients with Acute Kidney Injury: A Systematic Literature Review - Intan Nurcahyani; Septanti, Risti; Maya Arfania (Eureka Herba Indonesia, 2023)
Acute kidney injury (AKI) is a serious health problem and can be life-threatening if not treated quickly and appropriately. There are several risk factors that can increase a person's chances of experiencing AKI. This study aimed to carry out a systematic review to explore the risk factors for acute kidney injury and the clinical course of acute kidney injury. The literature search process was carried out on various databases (PubMed, Web of Sciences, EMBASE, Cochrane Libraries, and Google Scholar) regarding risk factors and clinical overview of acute kidney injury. The search was performed using the terms: (1) " risk factors " OR " Clinical" OR" symptoms " OR" sign " AND (2) " acute kidney injury". There are several risk factors that can increase a person's chances of experiencing acute kidney injury (AKI). These factors can be intrinsic (inside the patient's body) or extrinsic (outside the patient's body). Patients with heart disease or other blood vessel diseases have a higher risk of developing AKI. Cardiovascular risk factors such as high blood pressure, coronary artery disease, heart failure, or chronic kidney disease can contribute to the development of AKI. In conclusion, acute kidney injury is caused by intrinsic and extrinsic risk factors. While the clinical course of patients with acute kidney injury begins with the prerenal, intrinsic, oliguric, diuretic, and recovery phases.